Supercritical CO2 Synthesis of Freestanding Se1-xSx Foamy Cathodes for High-Performance Li-Se1-xSx Battery - Lu, Chengwei; Fang, Ruyi; Wang, Kun; Xiao, Zhen; kumar, G. Gnana; Gan, Yongping; He, Xinping; Huang, Hui; Zhang, Wenkui; Xia, Yang (Frontiers in Chemistry, 2021)
Selenium-sulfur solid solutions (Se1-xSx) are considered to be a new class of promising cathodic materials for high-performance rechargeable lithium batteries owing to their superior electric conductivity than S and higher theoretical specific capacity than Se. In this work, high-performance Li-Se1-xSx batteries employed freestanding cathodes by encapsulating Se1-xSx in a N-doped carbon framework with three-dimensional (3D) interconnected porous structure (NC@SWCNTs) are proposed. Se1-xSx is uniformly dispersed in 3D porous carbon matrix with the assistance of supercritical CO2 (SC-CO2) technique. Impressively, NC@SWCNTs host not only provides spatial confinement for Se1-xSx and efficient physical/chemical adsorption of intermediates, but also offers a highly conductive framework to facilitate ion/electron transport. More importantly, the Se/S ratio of Se1-xSx plays an important role on the electrochemical performance of Li-Se1-xSx batteries. Benefiting from the rationally designed structure and chemical composition, NC@SWCNTs@Se0.2S0.8 cathode exhibits excellent cyclic stability (632 mA h g-1@200 cycle@0.2 A g-1) and superior rate capability (415 mA h g-1@2.0 A g-1) in carbonate-based electrolyte. This novel NC@SWCNTs@Se0.2S0.8 cathode not only introduces a new strategy to design high-performance cathodes, but also provides a new approach to fabricate freestanding cathodes towards practical applications of high-energy-density rechargeable batteries.